Development of effective water-management institutions: final report, vol. V, appendix III: towards water sector reforms: policy case study on the Philippines, Sri Lanka and Thailand - International Water Management Institute (International Water Management Institute, 2003)
Regional study implemented by IWMI with financial support from the Asian Development Bank (RETA 5812)